A Survey on Outcomes of Patients Operated with Kocher Approach in the Posterior Acetabulum Wall Fractures - Seyed Mir Mansour Moazen Jamshidi; Shayan Ghorbani (Journal of Orthopedic and Spine Trauma)
Acetabular fractures are among the most common fractures in pelvic injuries. These types of fractures are mostly caused by high energy impact. Considering that there are many challenges in using the type of treatment method in acetabular fractures and the incorrect treatment of these fractures can have many complications for the patient. In this regard, we decided to conduct a study to examine the treatment results of patients who underwent surgery with a posterior approach. method To do this, the files of patients admitted to the orthopedic department of the hospital were examined. After contacting the patients and obtaining consent to participate in the study and explaining the work steps, for measurement Performance outcomes in the examination 6 months after the treatment results and final follow-up, the hip score index (Harris hip score) was used, which includes the four main parts of pain, the patient's performance during activities, different degrees of deformity, and range of motion of the hip joint. The scores were graded in four categories: excellent (100-90), good (89-80), average (79-70) and poor less than (70). It was entered into SPSS software and analyzed. Conclusion In this study, the total number of patients was 25, of which 80% were men and 20% were women. Our patients were generally in the age group of 10-60 years, respectively, 12% in the age group of 10-20 years, 32% in the age group of 21-30 years, 36%, in the age group of 31-40 years, 12% were in the age group of 41-50 years and 8% were in the age group of 51-60 years. Treatment results were evaluated as good or excellent in 15 (60%) patients. Treatment results had no statistically significant relationship with age and sex. 48% have no pain and lameness and the others show different degrees of pain. 96% of the people were able to climb the stairs, but 4% were unable to climb the stairs. 76% of the people had the ability to use public transportation and the rest of the people did not. 40% of the people did not need to use crutches and the rest of the people depended on crutches to varying degrees. According to the therapeutic results obtained from the surgery, it can be concluded that this surgery has acceptable results finds out.